2020
DOI: 10.3390/fluids5020065
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Soliton Interactions on the Surface of Deep Water

Abstract: The paper presents the long-time dynamics with multiple collisions of breathers in the super compact Zakharov equation for unidirectional deep water waves. Solutions in the form of breathers were found numerically by the Petviashvili method. In the terms of envelope and the assumption of the narrow spectral width the super compact equation turns into the well known exact integrable model—nonlinear Schrödinger equation, and the breather solution in this case turns into envelope soliton. The results of numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…It was observed for the first time in [25] that a collision of two single breathers with very close velocities could result in the formation of a periodically oscillating structure resembling the NLSE bi-soliton. Therefore, the obvious step to obtain the bound structure is to take two single breathers and then set them at the same point in space as initial conditions.…”
Section: Bound Structures In the Super Compact Dyachenko-zakharov Equmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed for the first time in [25] that a collision of two single breathers with very close velocities could result in the formation of a periodically oscillating structure resembling the NLSE bi-soliton. Therefore, the obvious step to obtain the bound structure is to take two single breathers and then set them at the same point in space as initial conditions.…”
Section: Bound Structures In the Super Compact Dyachenko-zakharov Equmentioning
confidence: 99%
“…It should be noted that, so far, in the SCDZE, only stable solutions in the form of a single breather are known. However, an unexpected result was obtained in [25], where multiple collisions of breathers in the periodic domain were studied. It was shown that the only one coherent structure remained at the end regardless of the breathers number and initial parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear Schrödinger (NLS) and Korteweg de Vries (KdV) equations are the classic examples of equations that admits solitary wave solutions [16,17]. The NLS equation originally arises in describing the propagation of narrow spectral wave packets on the fluid boundary in a gravitational field [16] (the soliton dynamics is studied in the recent works [18][19][20]). The KdV equation describes nonlinear waves in the long-wave region of the spectrum, that is, where the length of surface perturbations is significantly greater than the depth of the fluid [17].…”
Section: Introductionmentioning
confidence: 99%
“…Three soliton collisions in warm magnetized plasmas were investigated in [13]. An increase in the number of interacting particles leads to rarefied and dense soliton gases [14][15][16][17][18][19][20][21][22][23][24][25]. An ensemble of interacting solitons can appear from the evolution of some initial conditions or as a result of modulation instability driven by random perturbations of an unstable plane wave.…”
Section: Introductionmentioning
confidence: 99%